THE INFLUENCE OF MEMORY SELF-EFFICACY AND ITS PERFORMANCE, IN THE SOCIAL PARTICIPATION OF OLDER ADULTS - Feldberg, Carolina; Stefani, Dorina (Anales de Psicología / Annals of Psychology, 2007)
The aim of this paper is to study the relation between memory self-efficacy beliefs and performance in memory tests, and its incidence in social participation. Participants and design: It was used an ex post facto-comparison group design. 200 older adults of medium socio-economic level, living in Buenos Aires city, Argentine, were interviewed. Instruments: Self-efficacy Verbal Episodic Memory Inventory, Memory Activities Inventory, Memory ca-pacity was assessed by The Rey Auditory Verbal Learning Test (RAVLT), and Logic Memory (Signoret Memory Battery). Results: Memory self efficacy beliefs have a stronger weight than memory capacity in older adult ´s social participation. Those who have positive beliefs about their memory capacity will participate more in social activities than those who have negative ones. Discussion: This results agree with other studies which identified the fac-tors that promote subjective well being in older adults. Social participation plays an important role in cognitive abilities enhancement.